2012
DOI: 10.7326/0003-4819-156-10-201205150-00011
|View full text |Cite
|
Sign up to set email alerts
|

How Variability in the Institutional Review Board Review Process Affects Minimal-Risk Multisite Health Services Research

Abstract: Background The Department of Health and Human Services recently called for public comment on human subjects research protections. Objective (1) To assess variability in reviews across Institutional Review Boards (IRBs) for a multisite minimal risk trial of financial incentives for evidence-based hypertension care. (2) To quantify the impact of review determinations on site participation, budget, and timeline. Design A natural experiment occurring from multiple IRBs reviewing the same protocol for a multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…[1][2][3][4] Multiple studies have demonstrated IRB variability in application of both the Code of Federal Regulations and the Health Insurance Portability and Accountability Act (HIPAA) Privacy Rule. [5][6][7][8][9][10] HIPAA requires authorization from patients for use of protected health information (PHI) for research but describes circumstances under which this requirement can be waived for "activities preparatory to research." 11 This waiver allows researchers to use PHI to identify and contact potential participants for recruitment purposes.…”
mentioning
confidence: 99%
“…[1][2][3][4] Multiple studies have demonstrated IRB variability in application of both the Code of Federal Regulations and the Health Insurance Portability and Accountability Act (HIPAA) Privacy Rule. [5][6][7][8][9][10] HIPAA requires authorization from patients for use of protected health information (PHI) for research but describes circumstances under which this requirement can be waived for "activities preparatory to research." 11 This waiver allows researchers to use PHI to identify and contact potential participants for recruitment purposes.…”
mentioning
confidence: 99%
“…Our study findings support several reports, mostly commentaries and personal perspectives, suggesting duplication and variability in the IRB review processes for multisite studies leading to research delays and burden placed on researchers. [1][2][3][4]8,9,13,14 Innovative streamlined IRB models are therefore needed to overcome the inefficiencies inherent in multisite studies.…”
Section: Commentmentioning
confidence: 99%
“…Options for centralized IRB are varied by commonly including a single central IRB, IRB reciprocity agreements between sites, and singlestudy cooperative agreements (regional or nonregional). 6,[9][10][11]15 However, barriers to the use of these mechanisms include low institutional level of comfort and trust of centralized IRB and concern about institutional liability for the IRB review. 16 Our data suggest the potential for single-study cooperative agreements, implemented on a study-by-study basis, to provide opportunities for enhanced efficiencies without compromise of subject rights and safety or protocol integrity.…”
Section: Commentmentioning
confidence: 99%
“…To ensure that science and knowledge can continue to advance while respecting the ethical principle of autonomy, we commonly asked substitute decision-makers (SDMs) to provide consent on patients' behalf [1,2]. In situations where a study is deemed to pose only minimal risk, for example, observational studies, some research ethics boards may waive the need for informed consent, although the criteria used to establish minimal risk have varied [3,4]. Studying interventions that must be administered on an emergency basis can further complicate the informed consent process due to the inability to identify SDMs within a suitable time frame [5].…”
mentioning
confidence: 99%